Quality of life and disease understanding: impact of attending a patient‐centered cancer symposium. (30th January 2015) - Padrnos, Leslie; Dueck, Amylou C.; Scherber, Robyn; Glassley, Pamela; Stigge, Rachel; Northfelt, Donald; Mikhael, Joseph; Aguirre, Annette; Bennett, Robert M.; Mesa, Ruben A.
<x xml:space="preserve">Abstract</x> A comprehensive cancer patient‐centered symposium comprised a broad population was surveyed on quality of life, symptoms, and disease‐specific knowledge before and after completed the symposium. This study revealed that a patient symposium, as an educational intervention improves a solid knowledge base amongst attendees regarding their disease, increases knowledge in symptom management, but may be insufficient to impact quality of life as a single intervention.